Nigeria : 2009 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; Statement by the IMF Staff Representative; and Statement by the Executive Director for Nigeria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2009 Article IV Consultation highlights that reforms initiated earlier this decade in Nigeria have averted the boom-bust pattern that characterized previous oil price cycles and better prepared the economy to deal with the global financial crisis. Non-oil growth averaged 9 percent from 2004 to 2008. The pace of economic activity has nevertheless slowed in 2009. Executive Directors have welcomed the authorities' commitment to a strong macroeconomic and financial policy framework that can support an early recovery and lay the basis for the successful implementation of Nigeria's Vision 2020 development plan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet